Компьютерное моделирование флуктуационных преобразований в полупроводниковых барьерах - Golovko, A. G. (PE "Politekhperiodika", Book and Journal Publishers, 2004)
The validity of the previously established regularity of fluctuation transformations in electronic devices with nonlinear voltage-current characteristics has been confirmed using computer modeling of the current dependence of the transformation of fluctuations in the concentration of mobile charge carriers and the saturation current into fluctuations in the voltage drop across p-n junctions.